Variation of isokinetic strength and bone mineral density in youth portuguese soccer players with age - Mota, S.; Brito, J.; Passos, E.; Marques, E.; Mota, J.; Seabra, A.; Rebelo, A. (The Open Sports Sciences Journal, 2010)
The aim of this study was to study the variation of isokinetic strength and bone mineral density on the lower limb in youth soccer players according to age level. Sixty-one youth male soccer players from three age groups (Under- 19, Under-17, and Under-15) take part on the study. Hamstrings and quadriceps concentric strength was evaluated by isokinetic dynamometry, and body composition was assessed using Dual energy X-ray absorptiometry. The t-test of matched pairs, ANOVA, and Bonferroni post hoc comparisons were applied to localize differences by age group Statistical criterion was set at 0.05. Strength and bone mineral density tended to develop with age with the furthest presenting higher values in the non dominant extremity in all age groups. Differences were found in peak torque of the quadriceps in the dominant limb between Under-15 and the other age groups (p<0.05). For the hamstrings peak torque and bone mineral density, differences were only found between the Under-19 and Under-15 (p<0.01). The Under-15 group diverged from the other two groups in the non-dominant limb in all variables. The non-dominant limb presented higher values of bone mineral density in all three groups (p<0.001). Bone mineral density seems to increase due to soccer practice, and this fact seems to be connected with strength development. Increasing muscle mass, which occurs with soccer practice, may increase the forces generated at the bones, thus leading to the development of bone mineral density.